Prescribing Peritoneal Dialysis for Elderly Patients Starting Peritoneal Dialysis - Andrew Davenport (Kidney and Dialysis)
Increased availability of dialysis services has led to both an increase in the number of elderly, frail, co-morbid patients with advanced chronic kidney disease now being offered dialysis and starting dialysis with residual kidney function. Traditionally, these patients would have been offered in-centre haemodialysis. However, the introduction of an assisted peritoneal dialysis service has allowed more of these elderly patients to be considered for peritoneal dialysis, a home-based treatment, with the exchanges performed by family members or visiting health care staff. It is now realised that the amount of dialytic clearance any individual requires varies, and as such, treatment targets have changed over time from achieving minimum clearance targets to a more holistic approach, considering patient lifestyles, and adapting dialysis prescriptions and schedules to the needs of the individual patient. As dietary intake is often lower in the elderly, coupled with the physiological loss of muscle mass, this results in a reduced generation of waste products of metabolism and consequently requires less dialytic clearance. Thus, this allows many elderly patients to benefit from an incremental approach to starting peritoneal dialysis, potentially beginning with only one or two continuous ambulatory peritoneal dialysis exchanges, or an overnight cycler for only a few nights/week.